Reconsidering West African migration: Changing focus from European immigration to intra-regional flows - Anne Sofie Westh Olsen (Danish Institute for International Studies (DIIS), 2011)
Research on West African migration has tended to focus on specific 'crisis migration' issues, such as trafficking, international refugee flows or irregular migration to Europe. This reflects rather Eurocentric policy priorities, since these forms of West African migration are actually relatively small in comparison with intra-regional migration. Indeed, for every 20 migrants who board trains and buses to West African destinations, only one will try to get on a boat to Europe. Therefore, the paper will focus on the migration from poorer to richer zones within the sub-region, specifically the composition of flows as well as ECOWAS (Economic Community of West African States) policy measures for mobility facilitation. Furthermore, the paper outlines future challenges and possibilities for West African migration, with West African nation states having experienced a demographic shock, high unemployment, and thus increased mobility pressures (both intra- and extra-regional). The analysis leads to a conclusion of why the European Union - based on a developmental perspective - should also be concerned with 'conventional' intraregional migration in West Africa.
Keywords: 300; Internationale Migration; Flüchtlinge; Westafrika